Editorial: A Reflective Take on The Government Decisions in Facing Global Uncertainty - Shadu Satwika Wijaya (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2023)
Editorial: Refleksi Keputusan Pemerintah dalam Menghadapi Ketidakpastian Global